Strategi Bisnis Kuliner Japan.pdg Dengan Pendekatan Business Model Canvas (BMC) di Kota Padang - Prima Fithri; Alizar Hasan; Septianas Yunior; Fandy Triawan (Jurnal Pembangunan Nagari, 2021)
Since the corona virus was declared a pandemic by the World Health Organization (WHO), the central government and local governments have issued policies and regulations aimed at breaking the chain of spreading the virus. The PSBB regulation has an impact on sales of Japan.pdg. During the pandemic, to be precise since mid-March 2020, Japan.pdg experienced a 42% decline in sales. For this reason, the purpose of this research will be to look at the design of new business strategies in the face of the Covid-19 pandemic. To achieve this, the method used in this research is the Business Model Canvas (BMC) method. Strategy formulation is carried out in 3 stages, namely input, process and matching stages. Finally, a Business Model Canvas (BMC) is designed based on the results of matching the strategies that have been obtained previously. The results obtained from this study are that Japan.pdg must maintain the quality of its products, add menus that are much needed by consumers during the pandemic, add brands/banners/booths in front of stores, so that they are easily accessible and seen by consumers, provide cheap, complete and affordable food packages. according to the economic conditions of the community. In addition, Japan.pdg needs to maximize promotions through social media such as Instagram, Facebook, and the use of WhatsApp business, add collaboration partners such as Grabfood so that they can reach other consumers, and provide special discounts and promos to attract consumers' attention.